Tracing the International Transmission of a Crisis Through Multinational Firms - Biermann, Marcus,Huber, Kilian (National Bureau of Economic Research, 2023)
We show that multinational firms transmit shocks across countries through their internal capital markets. We study a credit supply shock to parent firms in Germany. International affiliates outside Germany supported their parents through internal lending, became financially constrained themselves, and experienced lower real growth. We find that managers were
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Multinationales Unternehmen; Interner Kapitalmarkt; Kapitalmobilität; Unternehmensfinanzierung; Fremdkapital; Finanzkrise; Betriebliche Finanzwirtschaft; Deutschland; Money and Interest Rates; International Factor Movements and International Business; International Finance; Financial Crises; Financial Institutions and Services; Corporate Finance and Governance